2018
DOI: 10.1021/acs.jpcb.8b01747
|View full text |Cite
|
Sign up to set email alerts
|

Designing Well-Structured Cyclic Pentapeptides Based on Sequence–Structure Relationships

Abstract: Cyclic peptides are a promising class of molecules for unique applications. Unfortunately, cyclic peptide design is severely limited by the difficulty in predicting the conformations they will adopt in solution. In this work, we use explicit-solvent molecular dynamics simulations to design well-structured cyclic peptides by studying their sequence-structure relationships. Critical to our approach is an enhanced sampling method that exploits the essential transitional motions of cyclic peptides to efficiently s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(44 citation statements)
references
References 81 publications
3
41
0
Order By: Relevance
“…2 D). These NOEs are consistent with types II and II 0 b turn structures at positions 5-6 and 2-3 (24), and these positions match the predicted positions for two type II b turns for P7 (residues 2-3 and 5-6, Fig. 1 A).…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…2 D). These NOEs are consistent with types II and II 0 b turn structures at positions 5-6 and 2-3 (24), and these positions match the predicted positions for two type II b turns for P7 (residues 2-3 and 5-6, Fig. 1 A).…”
Section: Resultssupporting
confidence: 82%
“…We found that for small CPs, two dihedral angles, either the f and j angles of the same residue (f i and j i ) or the j angle of one residue and the f angle of the next residue (j i and f iþ1 ), need to change coherently to enable conformational switches. By targeting these essential transitional motions using bias-exchange metadynamics (BE-META) simulations, we can efficiently sample the conformational space of a CP (22)(23)(24). Using this method, we started examining CP sequence-structure relationships with explicit-water molecular dynamics (MD) simulations by gradually substituting Gly residues in cyclo-(GGGGGG) with Val.…”
Section: Introductionmentioning
confidence: 99%
“…Since the late 1990s, using manual design and trial-and-error synthesis, the Gellman group has discovered many peptide 'foldamers,' or rigid linear peptide scaffolds that can be functionalized [91][92][93]. Others, such as the Kritzer group, have pursued linear and cyclic foldamers able to bind to target proteins [94,95]. Despite these successes, extensive exploration of sequence and conformation space has been hindered by the lack of robust computational methods.…”
Section: The Development Of Peptide Macrocycle Design Methods That Yimentioning
confidence: 99%
“…3), which can predict the crystal structures of 17 out of these 20 CPs with backbone RMSD < 1.1 Å, and 8 CPs with backbone RMSD < 0.5Å. Metadynamics with RSFF2 was used recently by Lin and coworkers to study sequence–structure relationships of some simple cyclic hexapeptides [90], and design well-structured cyclic pentapeptides [105]. REMD with RSFF2 has also been used to study α-helical stapled peptides, together with GAFF to describe the non-standard amino acids, giving prediction in excellent agreements with experimental observations [[106], [107], [108]].…”
Section: Peptide Structure Predictionmentioning
confidence: 99%